KinoFabula Essais sur la littérature et le cinéma russes - Géry, Catherine (EuropeS, 2016)
The essays in this anthology examine the images of cinema in light of their original and ever-changing relationship with literature in all its forms (fables, oral tales, poetry, theatre and novels). They analyze the different types of relationships and circulation that enable dialogue between works: inter-genre relationships (the cinematic fable, skaz or poem, etc.); intermedial relationships between the words of literature and the images of cinema, which are an a posteriori commentary on the former but also retroactively encourage a semantic return to the texts and tell us about their interpretative regime; and temporal relationships that embed history (the historical past) in stories (the present of the fictional enunciation). The works that thereby enter into dialogue are considered as (textual or visual) spaces of transition, as eternally imperfect and unfinished objects that nevertheless each aspire to completion, in the same way that, according to Walter Benjamin, a translation completes the "original" text and reveals its mode of intention. By adding themselves to one another, commenting on one another, translating one another or rewriting one another, literary and visual works feed into the very movement of culture, which is constantly "hybridizing" and reinterpreting its own content.